Preparation of a 3D Janus sponge for emulsion separation and dye adsorption
Through the preparation of the 3D Janus sponge, the modification of its super -friendly and ultra -sparse water side is used to solve the problem of hydrophilic separation and low dye adsorption efficiency in existing technology, and realize the separation of high -throughput, high -efficiency oil and water emulsion and dye adsorption. It is suitable for the removal of a variety of pollutants.
Patent Information
- Application Number
- CN202310277507.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-21
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-03-21
AI Technical Summary
The prior art has problems such as low separation flux, short service life and single application range in oil-water separation and dye adsorption, and it is difficult to effectively remove a variety of pollutants.
The preparation method of 3D Janus sponge is adopted, and the transformation of polyurethane sponge and the superficial water side of the polyurethane sponge forms a 3D structure of the ultra -hydrophobic structure on one side of the super -intimated side to achieve the efficient separation of oil and water emulsion and the adsorption of dyes.
Oil and water emulsion is separated by high -throughput, high separation efficiency, and has excellent dye adsorption performance. It is suitable for the removal of a variety of pollutants, and has good circulation stability and recycling performance.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oil-water separation, and specifically relates to a preparation method and application of a 3D Janus sponge for efficient emulsion separation and dye adsorption. Background Art
[0002] The environmental degradation caused by the development of human society and the progress of science and technology has become a global problem. The oily water pollution has become one of the most difficult problems that endanger the environment, mainly due to the increasing discharge of various oily wastewaters from the industrial and catering industries, as well as the frequent occurrence of oil spills. At the same time, dye wastewater, mainly produced by the printing, textile and semiconductor industries, is another dangerous water pollutant. Due to the characteristics of dyes such as toxicity, non-biodegradability, carcinogenicity and mutagenicity, they pose a serious threat to organisms. Therefore, it is urgent to develop materials and technologies for effective wastewater purification that can remove multiple pollutants at the same time.
[0003] Chinese patent CN111001190 A discloses a method for preparing an emulsion separation membrane with controllable wettability and its application. It is characterized in that a cobalt salt is used as an electrolyte, and multilayer cobalt hydroxide nanosheets are self-assembled and deposited on the surface of a stainless steel mesh by an electrodeposition technique, and the surface is modified by fluorosilane to obtain an emulsion separation membrane with controllable wettability, and the separation efficiency of oil-in-water and water-in-oil emulsions is more than 99.5%. Although the present invention has controllable wettability, due to its assembly deposition modification on a stainless steel mesh, the porosity is low and the separation channel is short, which will block the channel, thereby making the separation membrane have a low separation flux and a short service life.
[0004] Chinese patent CN111068523 A discloses a high-throughput emulsion separation composite material and its preparation method and application. It is characterized in that the fiber pulp is constructed into a porous membrane structure by vacuum membrane forming technology and then hydrophobically modified to obtain a high-throughput emulsion separation material. Although the porous 3D structure is used in the present invention, it can only separate a single oil-in-water emulsion, which limits its application range.
[0005] Chinese patent CN110655676 A discloses a method for preparing a super-hydrophobic sponge with an emulsion separation function. It is characterized in that a commercial polymer sponge is sequentially immersed in a prepared polyacrylic acid, a chitosan solution, and a suspension containing magnesium hydroxide, and then the sponge obtained above is treated with a surfactant containing a low surface energy to obtain a super-hydrophobic sponge for emulsion separation. The present invention is easy to operate and utilizes the porous structure of the sponge, but its use is single and it is difficult to achieve multifunctionality.
[0006] Based on the above problems, the present invention designs a 3D Janus sponge, which can separate surfactant-stabilized water-in-oil emulsions and oil-in-water emulsions, and is a multi-purpose material with high throughput, high separation efficiency and the ability to remove multiple pollutants at the same time. Summary of the invention
[0007] In order to overcome the shortcomings and deficiencies of the above-mentioned prior art and preparation methods, the primary purpose of the present invention is to provide a 3D Janus sponge preparation technology that is simple to operate, durable, has a long life, high separation efficiency, excellent dye adsorption performance, high throughput, can be stored for a long time at room temperature, and has good cycle stability and recovery performance, and can simultaneously achieve oil-in-water and water-in-oil emulsion separation and dye adsorption.
[0008] In order to achieve the above object, the present invention provides the following technical solutions:
[0009] 1. A method for preparing a 3D Janus sponge for separating oil / water emulsions and dyes, comprising the following steps:
[0010] (1) Superhydrophilic modification of polyurethane sponge
[0011] ① Wash the polyurethane sponge with deionized water and anhydrous ethanol in a ratio of 1:1, and finally put it in a 40 ℃ oven to dry for later use;
[0012] ②Dissolve chitosan with a mass concentration of 2.5% to 10% in a 0.1% to 0.5% glacial acetic acid aqueous solution, adjust the pH to neutral, dissolve protocatechuic acid with a mass concentration of 1% to 3% in deionized water containing Tris-HCl, wait for the two to be completely dissolved and mix, and add an oxidant to dissolve. Place the polyurethane sponge pretreated in ① in the solution, perform chemical co-deposition at 60°C for 4 to 6 hours, and finally dry to obtain a super-hydrophilic sponge;
[0013] (2) Modification of the superhydrophobic side
[0014] Dissolve 5% to 10% stearic acid and 3% to 10% titanium dioxide in 20 ml of anhydrous ethanol solution to form a suspension. Immerse one side of the superhydrophilic sponge in (1) in the suspension to form a superhydrophobic side through coordination reaction between stearic acid and titanium dioxide. Finally, dry the sponge to obtain a 3D Janus sponge with one side superhydrophobic and the other side superhydrophilic.
[0015] The polyurethane sponge has the characteristics of low cost, light weight, small pore size, high adsorption capacity, good elasticity, etc.
[0016] In the step (1), the polyurethane sponge is cleaned in an ultrasonic bath with a 1:1 ratio of deionized water and anhydrous ethanol for 30 to 40 minutes.
[0017] In the step (1), the pH value is adjusted to neutral using sodium hydroxide.
[0018] In the step (1), the pH of Tris-HCl in deionized water is 8.5.
[0019] In the step (1), the oxidant is one of ammonium persulfate or potassium persulfate.
[0020] In step (2), one side of the super-hydrophilic sponge is immersed in anhydrous ethanol suspension, and the sponge absorbs no more than 50% of its own height.
[0021] The beneficial effects of the present invention are: compared with the prior art, the advantages of the present invention are:
[0022] 1) The preparation process is simple, the raw materials are readily available, and the cost is low;
[0023] 2) The prepared 3D Janus sponge has the characteristics of controllable wettability and can be used to separate surfactant-stabilized oil-in-water emulsions as well as oil-in-water emulsions;
[0024] 3) The prepared 3D Janus sponge has the characteristics of high separation speed compared with membranes or other materials used for separation of oil-in-water or water-in-oil emulsions alone. This is because the 3D Janus structure is subjected to capillary force in addition to hydrostatic pressure during the separation process;
[0025] 4) The prepared 3D Janus sponge, due to its interconnected cage structure, ultra-high porosity and tortuous permeation channels, enables emulsion droplets or organic dyes to be effectively intercepted and adsorbed when passing through the permeation channels, thereby achieving high separation efficiency;
[0026] 5) The prepared 3D Janus sponge will undergo a squeezing process during the separation process. The separation efficiency and flux will vary with the degree of squeezing;
[0027] 6) The prepared 3D Janus sponge can be stably used in different pH and salt environments;
[0028] 7) The prepared 3D Janus sponge can simultaneously separate mixed pollutants such as emulsions and dyes during the separation process;
[0029] In the application, the oil phase for emulsion separation can be selected from epoxidized soybean oil, n-hexane, dodecane, vacuum pump oil, isooctane and the like. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further described below in conjunction with embodiments;
[0031] Example 1
[0032] A 3D Janus sponge for separating oil / water emulsion and dye is prepared by the following steps:
[0033] (1) Hydrophilic modification of polyurethane sponge
[0034] ① The super-hydrophobic polyurethane sponge was cleaned in an ultrasonic bath with deionized water and anhydrous ethanol in a ratio of 1:1 for 1 h, and then dried in a 40 °C oven for later use;
[0035] ② Dissolve chitosan with a mass concentration of 2.5% in 100ml of deionized water, add 100μl of glacial acetic acid to completely dissolve it, then adjust the pH to neutral with sodium hydroxide at pH=13, dissolve 0.3g of protocatechuic acid in a deionized water solution of Tris-HCl at pH=8.5, mix them after they are completely dissolved, add ammonium persulfate with a mass concentration of 1% for oxidation, and after the oxidant is completely dissolved, place the polyurethane sponge pretreated in ① in the mixed solution, perform chemical co-deposition at 60°C for 24h, and finally dry at 60°C to obtain a superhydrophilic sponge;
[0036] (2) Modification of the superhydrophobic side
[0037] Dissolve 0.4 g of stearic acid and 0.4 g of titanium dioxide in 20 ml of anhydrous ethanol to form a suspension. Immerse one side of the superhydrophilic sponge in (1) in the suspension to form a superhydrophobic side through coordination reaction between stearic acid and titanium dioxide, and then dry the superhydrophobic side to obtain a 3D Janus sponge with one side being superhydrophobic and the other side being superhydrophilic.
[0038] Example 2
[0039] (1) Hydrophilic modification of polyurethane sponge
[0040] ① The super-hydrophobic polyurethane sponge was cleaned in an ultrasonic bath with deionized water and anhydrous ethanol in a ratio of 1:1 for 1 h, and then dried in a 40 °C oven for later use;
[0041] ② Dissolve 5% chitosan in 100ml deionized water, add 200μl glacial acetic acid to completely dissolve it, then adjust the pH to neutral with pH=13 sodium hydroxide, dissolve 0.3g protocatechuic acid in a deionized water solution of Tris-HCl at pH=8.5, mix them after they are completely dissolved, add 1% ammonium persulfate for oxidation, after the oxidant is completely dissolved, place the polyurethane sponge pretreated in ① in the mixed solution, perform chemical co-deposition at 60℃ for 6h, and finally dry at 60℃ to obtain a superhydrophilic sponge;
[0042] (2) Modification of the superhydrophobic side
[0043] Dissolve 0.4 g of stearic acid and 0.4 g of titanium dioxide in 20 ml of anhydrous ethanol to form a suspension. Immerse one side of the superhydrophilic sponge in (1) in the suspension to form a superhydrophobic side through coordination reaction between stearic acid and titanium dioxide, and then dry the superhydrophobic side to obtain a 3D Janus sponge with one side being superhydrophobic and the other side being superhydrophilic.
[0044] Example 3
[0045] (1) Hydrophilic modification of polyurethane sponge
[0046] ① The super-hydrophobic polyurethane sponge was cleaned in an ultrasonic bath with deionized water and anhydrous ethanol in a ratio of 1:1 for 1 h, and then dried in a 40 °C oven for later use;
[0047] ② Dissolve 10% chitosan in 100ml deionized water, add 300μl glacial acetic acid to completely dissolve it, then adjust the pH to neutral with pH=13 sodium hydroxide, dissolve 0.3g protocatechuic acid in a deionized water solution of Tris-HCl at pH=8.5, mix them after they are completely dissolved, add ammonium persulfate for oxidation, and after the oxidant is completely dissolved, place the polyurethane sponge pretreated in ① in the mixed solution, perform chemical co-deposition at 60℃ for 5h, and finally dry at 60℃ to obtain a superhydrophilic sponge;
[0048] (2) Modification of the superhydrophobic side
[0049] Dissolve 0.4 g of stearic acid and 0.4 g of titanium dioxide in 20 ml of anhydrous ethanol to form a suspension. Immerse one side of the superhydrophilic sponge in (1) in the suspension to form a superhydrophobic side through coordination reaction between stearic acid and titanium dioxide, and then dry the superhydrophobic side to obtain a 3D Janus sponge with one side being superhydrophobic and the other side being superhydrophilic.
[0050] 3D Janus sponge performance test
[0051] The following comparative tests were conducted according to the different concentrations of chitosan in the above-mentioned Examples 1, 2 and 3. Taking the super-hydrophilic side of the 3D Janus sponge as an example, the test results are shown in Table 1.
[0052] Method for measuring water contact angle: JC2000G contact angle / interfacial tension tester was used for measurement. The contact angle of oil (n-hexane) under water on the hydrophilic side and the contact angle of water under oil (n-hexane) on the hydrophobic side of each sample were measured 5 times and the average value was taken.
[0053] Method for determining separation flux: A homemade compression separation device was used to control the sponge compression degree to 90%, and 20 ml of each of water-in-oil and oil-in-water emulsions were separated. The separation flux was calculated according to the following formula:
[0054] Flux = V / AT
[0055] Where V is the volume of the permeate (L), T is the time (h), and A is the cross-sectional area (m 2 ).
[0056] Separation efficiency determination method: JH-OIL-8 infrared spectrophotometer was used for determination. 5 ml of the emulsion before separation and the filtrate after separation were extracted with tetrachloroethylene respectively. The separation efficiency was calculated according to the following formula:
[0057] Separation efficiency(%) = (1− C0 / C f )*100%
[0058] Among them, C f and C0 are the concentrations of contaminants in the filtrate and feed, respectively.
[0059] The determination method of dye adsorption efficiency is as follows: L8 UV spectrophotometer is used for determination, and different concentrations of methylene blue are used to measure the absorbance to make a standard curve. The concentration of the dye after separation is calculated according to the standard curve, and finally the dye removal efficiency is calculated according to the following formula:
[0060] Removal efficiency(%) =(1-N1 / N0)*100%
[0061] Where N0 and N1 are the concentrations of the dye before and after separation, respectively.
[0062] Table 1 Effect of different chitosan dosage on the properties of 3D Janus sponge
[0063] Chitosan dosage m / % Super hydrophilic side Under water OCA (°) <![CDATA[Ultra-hydrophilic side Flux ( Lm − 2 h − 1 )]]> Super hydrophilic side separation efficiency (%) Dye removal efficiency (%) 2.5 156.7 13500 99.6 99.5 5 158.3 15600 99.7 99.8 10 164.1 11100 99.8 99.4
Claims
1. A method for preparing a 3D Janus sponge for emulsion separation and dye adsorption, comprising the following steps: (1) Superhydrophilic modification of polyurethane sponge ① Clean the super-hydrophobic polyurethane sponge with deionized water and anhydrous ethanol in a 1:1 ratio in an ultrasonic oven, and finally dry it in a 40°C oven for later use; ② Dissolve chitosan with a mass concentration of 2.5% to 10% in a 0.1% to 0.5% glacial acetic acid aqueous solution, and dissolve protocatechuic acid with a mass concentration of 1% to 3% in deionized water of Tris-HCl. After the two are completely dissolved, mix them. After mixing evenly, add an oxidant with a mass concentration of 1% for oxidation. After the oxidant is completely dissolved, place the dried polyurethane sponge in the solution, perform chemical co-deposition at 60°C for 4 to 24 hours, and finally dry it to obtain a super hydrophilic sponge. (2) Modification of the superhydrophobic side Stearic acid with a mass concentration of 5% to 10% and titanium dioxide with a mass concentration of 3% to 10% are dissolved in 20 to 30 ml of anhydrous ethanol solution to form a suspension. One side of the superhydrophilic sponge in (1) is immersed in the above suspension to form a superhydrophobic side through coordination reaction between stearic acid and titanium dioxide. Finally, the sponge is dried to obtain a 3D Janus sponge with one side being superhydrophobic and the other side being superhydrophilic.
2. The method for preparing a 3D Janus sponge for separating emulsions and adsorbing dyes according to claim 1, characterized in that: In the above (1), the pH of the deionized water prepared with Tris-HCl is 8.
5.
3. The method for preparing a 3D Janus sponge for separating emulsions and adsorbing dyes according to claim 1, characterized in that: The oxidant added in the above-mentioned (1) is one of ammonium persulfate or potassium persulfate.
4. The method for preparing a 3D Janus sponge for separating emulsions and adsorbing dyes according to claim 1, characterized in that: The mass concentration of chitosan added in the (1) is 2.5%.
5. The method for preparing a 3D Janus sponge for separating emulsions and dye adsorption according to claim 1, characterized in that: The mass concentration of chitosan added in the (1) is 5%.
6. The method for preparing a 3D Janus sponge for separating emulsions and adsorbing dyes according to claim 1, characterized in that: The mass concentration of chitosan added in the (1) is 10%.
7. Application of the 3D Janus sponge prepared according to the preparation method according to any one of claims 1 to 6 in emulsion separation and dye adsorption.
8. The use according to claim 7, characterized in that: The hydrophobic phase involved in the emulsion separation is selected from one or more of soybean oil, vacuum pump oil, isooctane and dodecane.
9. The use according to claim 7, characterized in that: In the dye adsorption, the dyes selected include methylene blue, rhodamine B, Congo red, and malachite green, and the concentrations thereof are all 10 mg / L.
Citation Information
Patent Citations
Preparation method of super-hydrophobic sponge with emulsion separation function
CN110655676A
Preparation method and application of emulsion separation film with controllable wettability
CN111001190A
High-flux emulsion separation composite material and preparation method and application thereof
CN111068523A
Preparation method of hydrogel coating for oil-water separation
CN113578720A
Device and method for solubilizing, separating, removing and reacting carboxylic acids in aqueous or organic solutions by means of micro- or nanoemulsification
EP2399885A1